Addressing sustainable development goals for confronting climate change: Insights and summary solutions in the stress stupidity system. (11th November 2020) - Sheppard, Jerry Paul; Young, Jesse
Abstract: We employ the concept of stupidity to address why more has not been done to address climate change and sustainable development. While the 'new' science of stupid has long existed in organizational studies, academicians have been too polite to call it that and organizational researchers historically labeled it the 'threat-rigidity effect.' With Alvesson and Spicer's 'stupidity-based theory of organizations' management researchers overcame this reluctance. In this work we explore what we will call the 'stress-stupidity system.' Building on the threat-rigidity effect, we outline the elements of the stress-stupidity system and look at how we may be able to 'fix stupid' to address issues of sustainability.